Dampak Sosial Ekonomi Program Perhutanan Sosial di LMDH Wono Asri KPH Kediri - Trison, Soni; Sundawati, Leti; Devi Yulianti, Septi; Refani, Afda; Ichwandi, Iin; Bahruni (Jurnal Hutan dan Masyarakat, 2024)
Social forestry is a sustainable forest management system in state forest areas carried out by the community to improve welfare, environmental balance, and social dynamics. This study aims to analyze the management system and the impact of social forestry on the community members of Forest Village Community Institution (LMDH) Wono Asri, at Forest Management Unit (KPH) Kediri. The descriptive statistical analysis based on public perception is used as the analysis method. A sample of 61 respondents was selected using the Slovin formula. Forest management included land preparation (100.00%), tillage (traditional system 95.08%), planting (100.00%, maintenance (weeding 100.00%, fertilizing 95.08%, pest and disease control 96.72%), harvesting (100.00%), and marketing (100.00%). Economic impact: farmer household income sources increased by 57.48%. Social impacts: changes in the use of forest products, decreased utilization, and development of resource use due to limited resources, increased community participation (95.08%), public perception of institutions (54.10%) and new jobs (100.00%). Environmental impacts: forest has been dominated by agroforestry plants (100.00%), low biodiversity (54.10%), environmental services that do not change much (60.66%), low potential disturbances and threats (70.49%), the existence of mitigation practices by the community due to the high number of natural disasters (49.18%). Farmers whom members of LMDH Wono Asri only sell their harvests, so there needs to improve the community's economy through processing of forest products.